INDONESIAN SOCIETY'S PERCEPTION OF HYPNOTHERAPY COMPARED TO OTHER TYPES OF PSYCHOTHERAPY: A POTENTIAL AND CHALLENGE - Jiemi Ardian (Journal of Psychiatry Psychology and Behavioral Research, 2022)
Background: Hypnotherapy has demonstrated high efficacy and is recognized for its potential for various clinical or health conditions. However, the perception of hypnotherapy among the general public is very diverse and influenced by many factors, especially compared to other types of psychotherapy. Objective: We aimed to investigate Indonesian society's perception of hypnotherapy compared to other types of psychotherapy. Methods: A cross-sectional survey design was used, targeting users of Twitter and Instagram. The chosen online questionnaires assessed variables, including respondents' characteristic data. This study also used the "Persepsi Praktik Hipnoterapi" questionnaire that has been peer-reviewed. Results: Among 100 participants, hypnotherapy is the most widely known, trusted (35%) type of psychotherapy. Most of the respondents had never undergone psychotherapy (36%). Moreover, most of the respondents in this study had never undergone hypnotherapy (71%). The majority of respondents also gave a possible response to hypnotherapy that can help to cure mental disorders (65%) and physical illnesses (54%) and heal permanently (55%). Most respondents responded "no" to the thought that hypnotherapy can replace the role of psychology and psychiatrists (86%). Conclusion: Respondents are more familiar with hypnotherapy than other psychotherapy techniques but many do not know the authority of hypnotherapists. Keywords: Hypnotherapy, Indonesia, perception, psychotherapy.